Britain, Malaysia And Southeast Asia: Past, Present And Future - Tarling, Nicholas (Penerbit Universiti Sains Malaysia (USM Press), 2010)
I want to thank Asia Pacific Research Unit (APRU), Universiti Sains Malaysia (USM) and Professor Ooi Keat Gin for bringing me to Penang again. It is always pleasant to be here. It is nearly fifty years since I first came, and there have been many changes. There were, of course, no USM, no APRU, and only, I fancy, a very small Ooi Keat Gin. But Penang has a respect for its past, and much of what I saw then I can still see. And the past goes back to the settlement of Georgetown and the building of Fort Cornwallis. Rambling round them a historian finds evocative. Who was there before? And why? Starting my study of the British in Malaysian history, not quite sixty years ago, under the guidance of an old Malayan Civil Service (MCS) hand, the late Victor Purcell, I was struck by the fact that I had to use, not only the records of the Colonial Office and Foreign Office in London, but also those of the East India Company and the India Office, then preserved in the Foreign Office itself, and now in the British Library.